Back Cover Image, Volume 92, Number 11, November 2020. Issue 11 (29th September 2020) - Liao, Yun; Li, Xueqi; Mou, Tangwei; Zhou, Xiaofang; Li, Dandan; Wang, Lichun; Zhang, Ying; Dong, Xingqi; Zheng, Huiwen; Guo, Lei; Liang, Yan; Jiang, Guorun; et al.
Abstract : Back Cover Caption : The cover image is based on the Research Article Distinct infecti on process of SARS‐CoV‐2 in human bronchial epithelial cell lines by Liao Y, Li X, Mou T, et al., https://doi.org/10.1002/jmv.26200 .